Disparities in cardiovascular disease prevalence among middle-aged and older adults: Roles of socioeconomic position, social connection, and behavioral and physiological risk factors - Zhang, Ji; Fang, Yian; Yao, Yao; Zhao, Yang; Yue, Dahai; Sung, Meekang; Jin, Yinzi; Zheng, Zhi-Jie (Frontiers in Cardiovascular Medicine, 2022)
ABSTRACT Introduction Cardiovascular disease (CVD) remains the leading cause of premature death globally and a major contributor to decreasing quality of life. In the present study, we investigated the contribution of social, behavioral, and physiological determinants of CVD and their different patterns among middle-aged and older adults. Methods We used harmonized data from 6 nationally representative individual-level longitudinal studies across 25 countries. We restricted the age to ≥50 years and defined cases as a self-reported history of CVD. The exposure variables were the demographic status (age and sex), socioeconomic position (education level, employment, and household income level), social connections (marital status and family size), behavioral factors (smoking, alcohol drinking, and frequency of moderate to vigorous physical activity), and physiological risk factors (obesity, presence of hypertension, and presence of diabetes). Mixed logistic regression models were fitted to investigate the associations, and dominance analysis was conducted to examine the relative contributions. Results In total, 413,203 observations were included in the final analysis, with the CVD prevalence ranging from 10.4% in Mexico to 28.8% in the United States. Physiological risk factors were the main driver of CVD prevalence with the highest dominance proportion, which was higher in developing countries (China, 57.5%; Mexico, 72.8%) than in developed regions (United States, England, 10 European countries, and South Korea). Socioeconomic position and behavioral factors also highly contributed but were less significant in developing countries than in developed regions. The relative contribution of socioeconomic position ranged from 9.4% in Mexico to 23.4% in the United States, and that of behavioral factors ranged from 5.7% in Mexico to 26.1% in England. Conclusion The present study demonstrated the different patterns of determinant contributions to CVD prevalence across developing and developed countries. With the challenges produced by different risk factors, the implementation of tailored prevention and control strategies will likely narrow disparities in the CVD prevalence by promoting health management and enhancing the capacity of health systems across different countries.